Siberprop : online course application and analysis system at Tuanku Bainun Library, Universiti Pendidikan Sultan Idris (UPSI) - Sulaiman, Khairul Asyrani; Ramli, Siti Sumaizan; Hashim, Afzanizam Dullah; Yaacob, Rusliza (Persatuan Pustakawan Malaysia, 2014)
Transformation in academic libraries involves new services, facilities and user engagement programs, including in-house systems development for library staff and users. Since the development of the Internet during the past four decades, libraries have transformed their roles to satisfy user requirements. Manual processes of library services are being converted to online systems to accelerate and further improve the effectiveness and delivery systems of library processes. The in-house systems developed by academic libraries specifically UPSI library aimed in providing enhanced and value-added delivery services to users. SiberPROP has been developed to manage user education classes and simplify current workflow for both users and administrators. Utilizing open source software development methodology, SiberPROP has proved an effective piece of technology that helps enrich library services.